Penyuluhan Hukum Tentang Keabsahan Perkawinan Pada Masyarakat di Kecamatan TNS Kabupaten Maluku Tengah - Barzah Latupono; Adonia Ivonne Laturette; Merry Tjoanda; Galang Djokdja (AIWADTHU: Jurnal Pengabdian Hukum, 2021)
Introduction: The rise of marriages that are carried out without going through the marriage procedure in the Marriage Law has resulted in many problems regarding the validity of marriage in the Central Maluku district, causing various legal problems in the local community.Purposes of Devotion: Providing legal understanding regarding the validity of marriage in communities in the TNS sub-district, Central Maluku district. Method of Devotion: Performed with the lecture method by each of the presenters. The lecturer is given time to deliver the material, after which the participants are invited to ask a problem or question, which is then answered in turn by the speaker according to the problem being asked.Results of the Devotion: It is important for all circles of society to understand the Marriage Law, this is so that the marriage is carried out in accordance with the law so that it can become a legal marriage.